(untitled) (Research, Society and Development, 2023)
In this article, we will present a qualitative survey of conceptual bases in a literature review of the categories of work and dialectics through the dialectical historical materialist conception. Our central objective is to relate the categories of work and dialectics as the foundation of the ontology of social being in the construction and use of the historical materialist method, emphasizing the development of man through work, the various concepts of dialectics, highlighting the relationship between the categories of work and dialectics in the construction of the dialectical historical materialist method and reflecting on the important relationship between man and work through an ontological perspective. We can also highlight the importance of different philosophers from Greece with the pre-Socratics to the emergence of the current scientific method of interpreting social phenomenon and reality, Karl Marx’s dialectical historical materialism. It was also possible to establish the importance of Marxist conceptual bases for understanding the ontology of social being, noting the impossibility of carrying out an in-depth study of man as a social being without associating the relationship between work, dialectics and historical materialism.